Cdc42‐Borg4‐Septin7 axis regulates HSC polarity and function. (18th October 2021) - Kandi, Ravinder; Senger, Katharina; Grigoryan, Ani; Soller, Karin; Sakk, Vadim; Schuster, Tanja; Eiwen, Karina; Menon, Manoj B; Gaestel, Matthias; Zheng, Yi; Florian, Maria Carolina; Geiger, Hartmut
Abstract: Aging of hematopoietic stem cells (HSCs) is caused by the elevated activity of the small RhoGTPase Cdc42 and an apolar distribution of proteins. Mechanisms by which Cdc42 activity controls polarity of HSCs are not known. Binder of RhoGTPases proteins (Borgs) are known effector proteins of Cdc42 that are able to regulate the cytoskeletal Septin network. Here, we show that Cdc42 interacts with Borg4, which in turn interacts with Septin7 to regulate the polar distribution of Cdc42, Borg4, and Septin7 within HSCs. Genetic deletion of either Borg4 or Septin7 results in a reduced frequency of HSCs polar for Cdc42 or Borg4 or Septin7, a reduced engraftment potential and decreased lymphoid‐primed multipotent progenitor (LMPP) frequency in the bone marrow. Taken together, our data identify a Cdc42‐Borg4‐Septin7 axis essential for the maintenance of polarity within HSCs and for HSC function and provide a rationale for further investigating the role of Borgs and Septins in the regulation of compartmentalization within stem cells. SYNOPSIS: A Cdc42‐Borg4‐Septin7 axis regulates the intracellular distribution of polarity proteins in HSCs. Either Borg4 or septin7 are critical for HSC function upon stress, suggesting a role in compartmentalization that is lost upon aging due to elevated Cdc42 activity. Cdc42 interacts with Borg4, which in turn interacts with Septin7 to regulate their polar distribution within HSCs. Lack of Borg4 or Septin7 in HSCs alters the distribution of Cdc42, likely by a feedback loop mechanism. HSCs devoid of Borg4 or Septin7 show reduced engraftment potential and hallmarks of aged HSCs. Abstract : A Cdc42‐Borg4‐Septin7 axis regulates the intracellular distribution of polarity proteins in HSCs. Either Borg4 or Septin7 are critical for HSC function upon stress, suggesting a role in compartmentalization that is lost upon aging due to elevated Cdc42 activity.